Disseminated Nocardiosis with Intracranial Mycotic Aneurysm in A Patient with Autoimmune Hepatitis: A Case Report and Review of The Literature - Pongkaew, Chaiwat; Apisarnthanarak, Anucha; Khawcharoenporn, Thana; Suwantarat, Nuntra; Rutjanawech, Sasinuch; Damronglert, Pansachee; Visuttichaikit, Suttichai (Asian Medical Journal and Alternative Medicine, 2024)
We are reporting a case of disseminated Nocardia otitidiscaviarum infection, manifesting as a ruptured intracranial aneurysm in an immunocompromised patient. The patient succumbed despite treatment with trimethoprim-sulfamethoxazole, amikacin, and levofloxacin along with surgical repairment. Nocardiosis should be one of the differential diagnoses for intracranial mycotic aneurysm among immunocompromised individuals. Running title: Nocardia intracranial aneurysm